One Europe, one neurologist? - GRISOLD, W. (2011)
Eur J Neurol. 2007 Mar;14(3):241-7. One Europe, one neurologist? Grisold W, Galvin R, Lisnic V, Lopes Lima J, Mueller E, Oberndorfer S, Vodusek DB; UEMS-EBN and EFNS Education Committee. Department of Neurology and Ludwig Boltzmann Institute for Neurooncology , Kaiser Franz Josef Hospital of the City of Vienna, Vienna, Austria. wolfgang.grisold@wienkav.at Abstract In recent years, there has been a major shift in emphasis within neurology from being a largely diagnostic discipline to one much more actively involved in treating disease. There have been major scientific advances leading to new and effective treatments. There is also a much greater awareness of the burden of neurological disease (Olesen J, Leonardi M. European Journal of Neurology 2003; 10: 471) and informed sufferers are requesting specific intervention. There is wide variation in the delivery of neurological services throughout Europe. This is reflected in manpower levels, the place of neurology related to other medical specialties and different mixes of hospital and private office practice. These differences have been thrown into sharper focus by the recent expansion of the European Union (EU). Initial training in neurology is given to undergraduate/pre-graduate students. Post-graduate education is delivered within a residency program leading to specialist qualification and certification. We now recognize that this is only the beginning of a life long program of continuous education and development (CME/CPD). National and international exchange programs facilitate the growth of knowledge and promote professional harmony and cooperation. The free migration of medical specialists has been an aspiration but remains limited by cultural, linguistic, personal, professional, political and economic factors. Two bodies, the European Board of Neurology (EBN-UEMS) http://www.uems-neuroboard.org (Union Européenne des Médecins Spécialistes) and the European Federation of Neurological Societies (EFNS) http://www.efns.org are actively involved in harmonising and developing neurology at the European level. PMID: 17355542 [PubMed - indexed for MEDLINE